Efficacy and safety of chimeric antigen receptor T cells targeting BCMA and GPRC5D in relapsed or refractory multiple myeloma - Xu Yang; Feiqing Wang; Feiqing Wang; Xiaoshuang Yuan; Bo Yang; Juan Chen; Jinyang Cheng; Guangyang Liu; Dongxin Tang; Xiao Xu; Sanbin Wang; Zhixu He; et al. (Frontiers in Immunology)
BackgroundClinical studies have demonstrated the high efficacy of using chimeric antigen receptor (CAR)-T cells targeting B-cell maturation antigen (BCMA) and orphan G protein-coupled receptor, class C group 5 member D (GPRC5D) to treat relapsed or refractory multiple myeloma (RRMM). In this study, we compared the efficacy and safety of BCMA CAR-T-cell therapy (BCMA CAR-T) and GPRC5D CAR T-cell therapy (GPRC5D CAR-T) in patients with RRMM.MethodsWe retrieved and included eligible clinical trials of BCMA or GPRC5D CAR-T for RRMM patients. The primary outcomes for efficacy were overall response rate (ORR), complete response rate (CRR), minimal residual disease (MRD) negativity, and relapse rate. The primary outcomes for safety were cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS).ResultsWe incorporated 18 early-phase, single-arm clinical trials, which included 503 and 133 patients receiving BCMA CAR-T and GPRC5D CAR-T, respectively. For the GPRC5D CAR-T cohort, the estimated ORR, CRR, MRD negativity rate, and relapse rate were found to be 89.8% [95% confidence interval (CI), 82.8%–96.9%], 50.5% (95% CI, 38.0%–62.9%), 78.8% (95% CI, 53.0%–100%), and 26.0% (95% CI, 7.4%–44.6%), respectively. In the BCMA CAR-T group, the ORR was 76.3% (95% CI, 67.9%–84.7%), the CRR was 34.3% (95% CI, 25.9%–42.7%), the MRD negativity rate was 76.5% (95% CI, 63.1%–90.0%), and the recurrence rate was 57.3% (95% CI, 47.7%–66.9%). These values were significantly lower than those observed in the GPRC5D CAR-T cohort. Both BCMA and GPRC5D CAR-T demonstrated acceptable safety. The estimated incidence of BCMA CAR-T resulting in grade 3–5 CRS and ICANS was only 5.4% (95% CI, 2.0%–10.4%) and 3.3% (95% CI, 0.6%–8.0%), respectively. The estimated incidence of GPRC5D CAR-T resulting in grade 3–5 CRS and ICANS was only 1.6% (95% CI, 0.0%–6.5%) and 2.7% (95% CI, 0.7%–6.2%), respectively.ConclusionGPRC5D CAR-T potentially demonstrates enhanced effectiveness relative to BCMA CAR-T in treating patients with RRMM. Therefore, GPRC5D CAR-T can be regarded as the preferred therapeutic option for RRMM, particularly among patients who have undergone relapse subsequent to BCMA CAR-T treatment.